LESSON LEARNED FROM THE PANDEMIC, REMEDIATION OF RADIO - Intan Soliha Ibrahim; Syahrudin Ag Ahmad; Haslinda Hasan; Lai Che Ching; Aisah Meri, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Radio research is not a new thing, and in fact, it was portrayed as an under-researched field. There is a long debate about radio acceptance, conventional radio migration to digital and will podcast kills conventional radio before the pandemic. However, pandemic Covid-19 affects the listenership of radio. At times of pandemics, radio has played a leading role, and throughout history, radio has been vital during major natural disasters and health emergencies. This research aims to recognise and address radio research's opportunities and challenges. A qualitative research approach is adopted through document analysis and observation. Findings show an increase in radio listening during the pandemic, the most flexible and accessible medium. Radio is the most versatile and experienced remediation at all times.